Advanced methods for selective investigation of neuronal circuitry: the future of developing novel therapeutic approaches in neuropharmacology? - Joksimović, Srdjan (Archives of Pharmacy, 2022)
Recent advances in neuroscience research techniques and methods have allowed researchers to study neuronal activity with unprecedented selectivity and temporal resolution. An important feature of these technical advances is targeting specific neuronal circuits in both healthy and diseased brains. Some of the most advanced methods include opto- and chemogenetics in freely behaving animals. Initially, they were designed as tools to help researchers understand better the mechanisms underlying complex behaviors, but these approaches may usher in a new era of pharmacological discovery in specific fields of neuroscience, such as epilepsy or neuropsychiatric disorders. Chemogenetics is based on a reverse logic compared to a traditional drug discovery process: an engineered drug target is introduced in the relevant brain area using a viral vector, thus enabling highly selective control of neuronal activity using an otherwise inert drug (e.g. clozapine N-oxide) in both loss- and gain-of-function experiments. In this manner, the researchers reduced the seizure activity in epileptic mice and improved cognitive impairments in a mouse model of schizophrenia. However, its application is largely limited to preclinical animal models, and it is still not clear whether chemogenetics can selectively modulate neuronal circuitry and serve as a potential therapeutic option in humans. A relative success of gene therapy has potentially resolved the issue of safely delivering an engineered receptor into the central nervous system, thus increasing its translational value. This presentation aims to summarize recent scientific evidence on the state-of-the-art and provide information on these advances that might stimulate a fruitful discussion during the conference.